2022
DOI: 10.17583/qre.10048
|View full text |Cite
|
Sign up to set email alerts
|

Deserción en la Educación Superior Rural: Análisis de Causas desde el Pensamiento Sistémico

Abstract: La deserción limita los beneficios personales y sociales de la educación. En este sentido, los estados e instituciones educativas buscan prevenir y mitigar este fenómeno mediante el desarrollo de políticas públicas e institucionales, sin embargo, la complejidad del fenómeno es tal, que estas políticas son insuficientes y no se encuentran del todo articuladas con las realidades de los estudiantes, de ahí que persistan las elevadas tasas de deserción. Así, el objetivo del presente artículo fue establecer las cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Regarding the increase in P&GO interventions resulting from changes in public policies regarding HEI quality criteria, there were no statistically significant differences for rural populations. This is due to the fact that the variables addressed in P&GO focus on academic, institutional, and individual (psychological) aspects that are difficult to modify through public policies, as stated by Guzmán et al, 66 Castleman & Meyer, 12 Ramírez et al, 34 and Lewine. 23 However, a simulation combining the three public policy options showed that their simultaneous application decreased dropout rates by up to 7.05%.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the increase in P&GO interventions resulting from changes in public policies regarding HEI quality criteria, there were no statistically significant differences for rural populations. This is due to the fact that the variables addressed in P&GO focus on academic, institutional, and individual (psychological) aspects that are difficult to modify through public policies, as stated by Guzmán et al, 66 Castleman & Meyer, 12 Ramírez et al, 34 and Lewine. 23 However, a simulation combining the three public policy options showed that their simultaneous application decreased dropout rates by up to 7.05%.…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, research addressed the complex issue of high dropout rates in education, recognizing it as a multifaceted phenomenon inadequately aligned with students' realities and educational policies. A conceptual model grounded in systems thinking was employed, highlighting variables such as work and family commitments, students' financial circumstances, and the role of educators as recurrent factors among participants [ 21 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%